2017
DOI: 10.1002/pra2.2017.14505401125
|View full text |Cite
|
Sign up to set email alerts
|

“Not what I thought!” information seeking behaviors of international students during the application for graduate study in the USA

Abstract: A recent study revealed that international students' reading comprehension scores on the Test of English as a Foreign Language (TOEFL) equates to 12 th -grade reading comprehension level (Taylor, 2017). In evaluating the admission materials at selected flagship universities in the United States, Taylor (2017) found that the reading comprehension level ranges from 15 thgrade to 19 th -grade level. The readability of these materials can be challenging to international graduate students. Though a large body of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…These variables included an international student admissions webpage, minimum TOEFL scores for admission, application fee, cost of attendance at the institution, visa information, housing opportunities, and if there was contact information for international students to engage with if they have a question during the application process. These information categories emerged from the data and were informed by the lived experiences of members of the research team who are currently international students studying in the United States, as well as extant research focused on information useful for international students seeking U.S. institutions (Huang & Bilal, 2017;Taylor & Bicak, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These variables included an international student admissions webpage, minimum TOEFL scores for admission, application fee, cost of attendance at the institution, visa information, housing opportunities, and if there was contact information for international students to engage with if they have a question during the application process. These information categories emerged from the data and were informed by the lived experiences of members of the research team who are currently international students studying in the United States, as well as extant research focused on information useful for international students seeking U.S. institutions (Huang & Bilal, 2017;Taylor & Bicak, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In a study of international undergraduate students, Huang and Bilal (2017) found that many international students often feel confused when navigating institutional websites, a very common source of information for prospective international students. These students claimed institutional websites were difficult to read and often lacked critical information necessary for application to the institution, such as housing information and minimum TOEFL requirements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the earlier 1980s, following the rapid development of China's economy, China's chorus industry has been developing fast. In particular, the chorus of the masses has been taken on a delightful situation both in terms of the popularity and singing level (Bregman, Patel & Gentner, 2016;Lavranos, Kostagiolas, Martzoukou & Papadatos, 2015;Huang & Bilal, 2017). It's well known that that the form of chorus art originated from Europe has a history of 500 or 600 years in the west.…”
mentioning
confidence: 99%